Adiposity, inflammation and fat‐soluble vitamins in adolescents - Rebecca Peixoto Paes‐Silva; Patrícia Calado Ferreira Pinheiro Gadelha; Maria da Conceição Chaves de Lemos; Célia Maria Machado Barbosa de Castro; Ilma Kruze Grande de Arruda; Alcides da Silva Diniz (Brazilian Society of Pediatrics, 2019)
Objective: Evaluate the association between inflammatory process, adiposity, and vitamins A, D, and E in adolescents, according to gender. Methods: Cross‐sectional study with adolescents aged 12-19 years old of both genders attending public schools in Recife. A questionnaire was used to collect data on socioeconomic level, lifestyle, and food intake of adolescents. Then, an anthropometric evaluation and a blood sampling were performed to analyze serum concentrations of α‐1‐acid glycoprotein, retinol, β‐carotene, α‐tocopherol, and 25‐hydroxy‐vitamin D. Results: The levels of α‐1‐acid glycoprotein were higher for abdominal obesity in both genders. Male adolescents with insufficient serum α‐tocopherol levels had low levels of α‐1‐acid glycoprotein (p = 0.03) and an increased risk of 25‐hydroxy‐vitamin D and β‐carotene deficiency in relation to total and abdominal fat; female adolescents had an increased risk of insufficient β‐carotene with abdominal obesity (PR: 1.33; 95% CI: 1.2-1.5). Conclusion: Abdominal adiposity implies a higher risk of inflammation and causes different changes to the levels of fat‐soluble vitamins according to gender. Resumo: Objetivo: Avaliar a associação entre processo inflamatório, adiposidade e as vitaminas A, D e E em adolescentes, segundo o sexo. Métodos: Estudo transversal com adolescentes de 12 a 19 anos de ambos os sexos de escolas públicas de Recife. Foi utilizado um questionário para coleta de dados socioeconômicos, de estilo de vida e de consumo alimentar dos adolescentes. Em seguida, realizou-se a avalição antropométrica e coleta de sangue para análise das concentrações séricas de α‐1‐glicoproteína ácida, retinol, β‐caroteno, α‐tocoferol e 25‐hidroxivitamina D. Resultados: Os níveis de α‐1‐glicoproteína ácida foram maiores na obesidade abdominal de ambos os sexos. Os meninos com níveis séricos insuficientes de α‐tocoferol expressaram níveis reduzidos de α‐1‐glicoproteína ácida (p = 0,03) e apresentaram um maior risco de deficiência de 25‐hidroxivitamina D e β‐caroteno na adiposidade total e abdominal, enquanto as meninas mostraram maior risco de insuficiência de β‐caroteno com a obesidade abdominal (RP 1,33; IC 95% 1,2‐1,5). Conclusão: A adiposidade abdominal reflete maior risco de inflamação e causa alterações distintas nas concentrações das vitaminas lipossolúveis, de acordo com o sexo. Keywords: Obesity, Inflammation, Adolescents, Vitamins, Palavras‐chave: Obesidade, Inflamação, Adolescentes, Vitaminas